Efficient and Selective Aerobic Oxidation of 5‐hydroxymethylfurfural to 2, 5‐diformylfuran at Moderate Reaction Conditions with Design of Experiments Approach. Issue 36 (22nd September 2022) - Derflinger, Christoph; Kamm, Birgit; Paulik, Christian; Meissner, Gisa; Spod, Hendrik
Abstract: Heterogeneous catalytic oxidation of 5‐hydroxymethylfurfural (HMF) with molecular oxygen to 2, 5‐diformylfuran (DFF) was performed on aluminium oxide‐supported ruthenium catalysts (Ru/Al2 O3 ). The ruthenium catalysts were analyzed by pH and Brunauer‐Emett‐Teller (BET) measurement, and potential side products measured by HPLC‐UV. High catalyst activity with near‐quantitative DFF yield (>99.9 %) was achieved in toluene under moderate reaction conditions (90 °C, 0.2 MPa O2 ). Various Al2 O3 supports were screened for optimal catalyst activity and selectivity for DFF, and the most effective was chosen for a Design of Experiments (DoE). With a central composite design based on a response‐surface model, the effects of reaction parameters (i. e., catalyst amount, oxygen pressure and temperature) on the reaction rate were investigated, and the selected model tested by analysis of variance (ANOVA). The modeling showed that catalyst amount had the highest relative impact on the reaction rate, and afforded in‐depth knowledge about the chemical space investigated. Abstract : In this study, various Ru/Al2 O3 catalysts were used for the aerobic heterogeneous oxidation of 5‐(hydroxymethl)furfural to 2, 5‐diformylfuran. With the help of the design of experiment approach, high catalyst activities with excellent product selectivity could be achieved under relatively moderate reaction conditions.